2021
DOI: 10.1111/jace.17667
|View full text |Cite
|
Sign up to set email alerts
|

High electromagnetic interference shielding effectiveness in MgO composites reinforced by aligned graphene platelets

Abstract: Graphene has been considered as an excellent filler to reinforce ceramics with enhanced properties. However, the uniform dispersion and controlled orientation of graphene sheets in a ceramic matrix have become major challenges toward higher performance. In this paper, we prepared MgO matrix composites with parallel graphene layers through the intercalation of the precursor into expandable graphite. We obtained a high electromagnetic interference (EMI) shielding effectiveness of ~30 dB, due to the multiple refl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…When EM radiation was passed through Fe nanoparticles in the MgO matrix, the shielding was excellent because of magnetic and dielectric properties and dispersion, with a maximum SE of −65.6 dB 28 . The average value of the EMI SET of pure MgO and 1, 3, 5 and 7 vol% graphene/ MgO are 5.78, 9.53, 21.88, 30.07 and 21.10 dB, respectively 29 …”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…When EM radiation was passed through Fe nanoparticles in the MgO matrix, the shielding was excellent because of magnetic and dielectric properties and dispersion, with a maximum SE of −65.6 dB 28 . The average value of the EMI SET of pure MgO and 1, 3, 5 and 7 vol% graphene/ MgO are 5.78, 9.53, 21.88, 30.07 and 21.10 dB, respectively 29 …”
Section: Introductionmentioning
confidence: 98%
“…28 The average value of the EMI SET of pure MgO and 1, 3, 5 and 7 vol% graphene/ MgO are 5.78, 9.53, 21.88, 30.07 and 21.10 dB, respectively. 29 The Ni nanoparticles are more suitable for EMI shielding as it possesses good magnetic and electrical properties and thermal stability. 30 The electrical conductivity nature of Nickel significantly influences the EM-SE by reflection losses.…”
Section: Introductionmentioning
confidence: 99%
“…The EG/Fe 3 O 4 composites were synthesized by a simple and convenient method we previously reported. 19,23 In a typical experiment, 11.4 g FeCl 3 and 7.0 g FeCl 2 ⋅4H 2 O at a molar ratio of 2:1 were dissolved in 80 mL deionized water, and 1 mL HCl was added to avoid the oxidation of Fe 2+ . Afterward, a 0.55 mL coupling agent dissolved in 20 mL ethanol was added to form the mixed solution of ceramic precursor.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, it is spatially isolated and can maintain two‐dimensional state at high temperature 16 . It was reported that the mechanical properties of MgO‐GNPs composites can be enhanced by controlling the directional arrangement of GNPs 17,18 . Furthermore, the addition of GNPs can also lead to an enhancement of the tribological properties of the composites 19 .…”
Section: Introductionmentioning
confidence: 99%
“…16 It was reported that the mechanical properties of MgO-GNPs composites can be enhanced by controlling the directional arrangement of GNPs. 17,18 Furthermore, the addition of GNPs can also lead to an enhancement of the tribological properties of the composites. 19 Therefore, GNPs might simultaneously play the role in reinforcing WC ceramics and reducing their friction wear.…”
Section: Introductionmentioning
confidence: 99%